The path walked (Ozone Therapy Global Journal, 2014)
When we look back we can measure with clarity how much we have advanced in the normative,associative, and training levels, and in common protocols for worldwide application of the ozonetherapy.Regularization of ozone therapyThe panorama that appeared before 2005 in relation to the practice of ozone therapy was bleak,there was literally nothing. The ozonetherapists were afraid, working practically in the dark, andadopting a low profile, to avoid arousing bad ideas by the health administrations. Researchwas conducted but for the authorities was not enough to demonstrate the safety and efficacyof the therapy.